Understanding dystonia: diagnostic issues and how to overcome them - Sarah Camargos; Francisco Cardoso (Arquivos de Neuro-Psiquiatria)
ABSTRACT The diagnosis and treatment of dystonia are challenging. This is likely due to gaps in the complete understanding of its pathophysiology, lack of animal models for translational studies, absence of a consistent pathological substrate and highly variable phenotypes and genotypes. The aim of this review article is to provide an overview of the clinical, neurophysiological and genetic features of dystonia that can help in the identification of this movement disorder, as well as in the differential diagnosis of the main forms of genetic dystonia. The variation of penetrance, age of onset, and topographic distribution of the disease in carriers of the same genetic mutation indicates that other factors – either genetic or environmental – might be involved in the development of symptoms. The growing knowledge of cell dysfunction in mutants may give insights into more effective therapeutic targets.